Pomenske spremembe pridevnika priden od 16. stoletja do danes - Tratar, Olga (Jezik in slovstvo, 2014)
The article presents the semantic changes in the adjective priden from the 16th century to the present day. In this period, the meaning spectrum of this denominal adjective has been reduced. While the prevailing original meaning of the lexeme priden was "useful", today the central meanings are "hard-working, diligent" and "fulfilling one's obligations or other people's expectations". The changes in meaning have been accompanied by changes in the collocational profile of the adjective, which, in the 16th century, predominantly collocated with a core noun containing the categorial component "-live", whereas today it collocates exclusively with nouns marked "+live".
Keywords: Slovene; slovenščina; priden (pridevnik); pridevniki; lastnostni pridevnik; pomenoslovje; zgodovinsko pomenoslovje; 16.st.